2014
DOI: 10.2478/amsc-2014-0051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Pressure ORE Grinding on the Efficiency of Flotation Operations

Abstract: This article discusses issues related to the impact of the high pressure comminution process on the efficiency of the copper ore flotation operations. HPGR technology improves the efficiency of mineral resource enrichment through a better liberation of useful components from waste rock as well as more efficient comminution of the material. Research programme included the run of a laboratory flotation process for HPGR crushing products at different levels of operating pressures and moisture content. The test re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The application of chemical reagents is not the only significant factor affecting the final flotation effect. As indicated works [14,15] the particle size distribution of feed material also plays a key role in the process. Properly selected communition and sizing processes provide a high level of copper minerals liberation, which guarantees better enrichment effects.…”
Section: Introductionmentioning
confidence: 90%
“…The application of chemical reagents is not the only significant factor affecting the final flotation effect. As indicated works [14,15] the particle size distribution of feed material also plays a key role in the process. Properly selected communition and sizing processes provide a high level of copper minerals liberation, which guarantees better enrichment effects.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, describing the subprocesses of flotation by the defined probabilities, which affect the rate of the process the value of flotation rate constant can be evaluated which indicate its relationship with the process parameters and properties of minerals. This value has a macroscopic character and should include information on the factors affecting the flotation process [122][123][124][125][126]. Available in the literature studies shown mainly flotation process, related to minerals flotation, as a fluid flow analysis or as a means of mass transport or as an unsteady process and creating models based on heuristic considerations [123], experimental data or numerical simulations [124].…”
Section: Particle In Three-phase Reactors Drawdown Of Floatingmentioning
confidence: 99%
“…(Schönert, 1988), the High Pressure Grinding Rolls have become in a modern and highly efficient technology. Applications of this equipment are related to the clinker cement industry in early stages (Kellerwessel, 1990;Hasanzadeh and Farzanegan, 2011) and after that, in mineral processing activities, especially in metallic ore deposits (Guevara and Menacho, 1992;Austin et al, 1993;Morrel et al, 1997;Torres and Casali 2009;Abouzeid and Fuerstenau, 2009;Saramak, 2011;Numbi and Xia, 2015). It is proven to reduce the operating costs in full scale plants when compared with other milling technologies, which is especially important with low-grade ores and inherent low efficiency of the conventional comminution system (Abouzeid and Fuerstenau, 2009;Liang et al, 2016;Lei et al, 2018).…”
Section: Hypothesismentioning
confidence: 99%
“…The literature shows several approaches to model HPGR particle size distribution. However, two of this approaches highlight for this type of machinery; when a single particle compression is combined with a batch grinding solution (Torres and Casali, 2009;Saramak, 2011) or by means of the calculation of several matrices between the differential feed and the breakage distribution function (Austin et al, 1993;Kodali et al, 2011). This study is based on the Austin (1993) model, but with modifications compared with the original expression:…”
Section: Test Designmentioning
confidence: 99%